Influência da infecção por Trypanosoma evansi sobre as colinesterases no sangue, plasma e cérebro de gatos - Silva, Aleksandro Schafer da (2009)
Changes in blood, plasma and brain cholinesterase activities in Trypanosoma evansi infected cats were investigated. Seven animals were infected with 108 trypomastigote forms each and six were used as control. Animals were monitored for 56 days by examining daily blood smears. The evolution of the disease was monitored by performing hematocrit measurements the day 0, 7, 21, 35 and 49. Blood samples were collected at days 28 and 56 post-inoculation to determine the activity of acetylcholinesterase (AChE) in blood and the activity of butyrylcholinesterase (BChE) in plasma. AChE was also evaluated in brain. A decrease in hematocrit values was observed in the T. evansi infected cats after day 7 (P < 0.05). The activity of AChE in blood and brain, and the activity of BChE in plasma significantly reduced in the infected cats. Therefore, the infection by T. evansi influenced cholinesterases of felines indicating changes in the responses of the cholinergic system.